Long-term follow-up of a randomized controlled trial on individualized fortification of human milk - Quan, Meiying; Zhang, Yu; Zhang, Lejia; Wang, Chen; Li, Zhenghong (Frontiers in Nutrition, 2026)
Background and aimsTo evaluate short- and long-term outcomes of preterm infants from a previous RCT on individualized fortification (IF).MethodsPreterm infants from the Peking Union Medical College Hospital (PUMCH) IF study were enrolled. Data before age 2 were collected from medical records. Long-term follow-up was conducted at ages 6–10 years. Growth and development outcomes as well as biochemical indexes were compared between IF and standard fortification (SF) groups.ResultsFifty-one infants completed 2-year follow-up. The IF group showed significantly better outcomes in head circumference z-scores at CA 6 months (p = 0.035), hemoglobin at CA 12 months (p = 0.044), and weight z-scores at CA 24 months (p = 0.027). Twenty-five children completed long-term follow-up. No significant differences were found in lung function, cognitive scores, ferritin, hemoglobin, IGF, 25-OH-vitamin D, bone age, or metabolic parameters including BMI and lipid profile.ConclusionPUMCH IF improved early growth outcomes, but no significant long-term health differences were observed.